Molecular dynamics of copolyester/clay nanocomposites as investigated by viscoelastic and dielectric analysis - Kalgaonkar, Rajendra A.; Jog, Jyoti Prakash (Journal of Polymer Science Part B-Polymer Physics, 2008)
We have investigated the molecular dynamics of poly(ethylene glycol-co-cycloxeane-1,4-dimethanol terephthalate) (PETG) nanocomposites based on a organically modified layered silicate. Intercalated namocomposites were prepared by melt compounding technique as evidenced from the X-ray diffraction and transmission electron microscopy studies. Two relaxation processes were observed in pure PETG as well as in the nanocomposites. The low-temperature beta-process was assigned to the local motions of C=O polar groups and the alpha-process was due to the glass-rubber transition or the segmental relaxations associated with the polymer chain backbone. Presence of layered silicates accelerated alpha-relaxation dynamics in the nanocomposites accompanied by a depression in T(g) which was attributed to the reduced intermolecular cooperativity between intercalated polymers chains. Additionally, a direct comparison between the viscoelastic and dielectric studies shows excellent agreement between the accelerated alpha dynamics of the nanocomposites. (C) 2008 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys 46: 2539-2555, 2008
Keywords: clay; Dielectric relaxation; Nanocomposites; polyesters

Synthesis of nickel-rubber nanocomposites and evaluation of their dielectric properties - Jamal, E. Muhammad Abdul; Joy, Pattayil Alias; Kurian, Philip; Anantharaman, Maliemadom R. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2009)
Nanocomposites based on natural rubber and nano-sized nickel were synthesized by incorporating nickel nanoparticles in a natural rubber matrix for various loadings of the filler. Structural, morphological, magnetic and mechanical properties of the composites were evaluated along with a detailed study of dielectric properties. It was found that nickel particles were uniformly distributed in the matrix without agglomeration resulting ill a magnetic nanocomposite. The elastic properties showed an improvement with increase in filler content but breaking stress and breaking strain were found to decrease. Dielectric permittivity was found to decrease with increase in frequency, and found to increase with increase in nickel loading. The decrease in permittivity with temperature is attributed to the high volume expansivity of rubber at elevated temperatures. Dielectric loss of blank rubber as well as the composites was found to increase with temperature. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Dielectric relaxation; Interfacial polarization; Nanocomposites